Liuwei Dihuang soft capsules attenuates endothelial cell apoptosis to prevent atherosclerosis through GPR30-mediated regulation in ovariectomized ApoE-deficient mice. (17th August 2017) - Jing, Yi; Cai, Danfeng; Chen, Qi; Xiong, Qingping; Hu, Tianhui; Yao, Yuan; Lin, Chao; Sun, Xin; Lu, Ying; Kong, Xueyun; Wu, Xiang; Li, Yu; et al.
Abstract: Ethnopharmacological relevance: Liuwei Dihuang (LWDH), a classical traditional Chinese medicine prescription, has been widely used to prevent and to treat various diseases with symptoms of 'Kidney-Yin' deficiency syndrome for over 1000 years in China. It is commonly used to treat functional decline associated with senile disease and menopausal syndrome, especially memory decline, insomnia, diabetes and osteoporosis. Modern experimental pharmacological studies indicated that the mechanism of LWDH treatment of menopausal syndrome may be associated with enhanced estrogenic effects. However, little attention has been paid to the potential impact of LWDH on atherosclerosis (AS) associated with female menopause. The aim of this study was to evaluate the preventive effects of LWDH intake on an animal model of female menopause AS and to explore the underlying molecular mechanism. Materials and methods: ApoE −/− mice were randomly divided into 4 groups, with C57BN/L6 mice as the control group. All ApoE −/− mice were ovariectomized (Ovx) one week prior to oral administration and initiation of high-fat diet. C57BL/6 mice were given sham operation and maintained on normal diet. The three administered groups were given simvastatin (4 mg/kg via i.g.) and LWDH (4.5, 9.0 g/kg via i.g.) every day for 14 weeks. Atherosclerotic lesions in the aortic root were determined by oil red O staining and hematoxylin-eosin staining. α-Actin and CD68 in atherosclerotic lesions were detected by immunohistological assay. Serum lipids and homocysteine (Hcy) levels were measured in the 14th week. The cleaved caspase-3, C/EBP homologous protein (CHOP) and G protein coupled estrogen receptor 30 (GPR30) expressions in the aortic arch endothelium were determined by immunohistochemistry and Western blot. The inhibitory effect of LWDH-medicated (20%, 12 h) on Hcy (20%, 24 h)-induced apoptosis of human umbilical vein endothelial cells (HUVECs) was examined by flow cytometry and Hoechst 33258 staining. Intracellular ROS production, nitric oxide release, and endothelial NO synthase (eNOS) activity were measured with or without LWDH-medicated serum pretreatment. In addition, CHOP, glucose-regulated protein GPR30, 78 (Grp78), Bcl-2, Bax and cleaved caspase-3 were analyzed by Western blot. Finally, the influence of G15, a specific antagonist of GPR30, on the protective effect of LWDH on endothelial cells was investigated. Results: In vivo administration of LWDH prevented plaque formation and reduced plasma lipid and Hcy levels. LWDH inhibited CHOP and cleaved caspase-3 expression in vivo and in vitro while maintaining GPR30 expression. In vitro study showed that Hcy-induced HUVECs apoptosis was weakened by LWDH-medicated serum pretreatment. Treatment with LWDH-medicated serum significantly upregulated NO release and eNOS activity in HUVECs. In addition, LWDH-medicated serum treatment optimized the balance between Bax and Bcl-2, and attenuated intracellular ROS production. G15 reversed the protective effect of LWDH on endothelial cells and the changes of apoptosis-related proteins. Conclusions: LWDH treatment can significantly reduce plaque formation in an animal model of menopausal AS. The mechanism may be inhibition of Hcy-induced endothelial cell apoptosis by modulating GPR30. Hence, LWDH can potentially be used to prevent AS-related vascular disease in menopausal women. Graphical abstract: